Preparation of Modified Montmorillonite and Nano TiO2 Composite Coating and Its Corrosion Resistance in Sodium Aluminate Solution - Wang, Hanli (Langmuir : the ACS journal of surfaces and colloids, 2025)
In this study, the corrosion environment in the evaporation stage of alumina production by the Bayer process was simulated, and TiO2-MMT/EP composite coating was prepared on the surface of Q235 steel. Montmorillonite (MMT) was functionalized via cation exchange and surface grafting using 3-aminopropyl triethoxysilane (KH550), enabling the introduction of organic groups onto the MMT surface and intercalation into its interlayer spacing. After compounding with titanium dioxide, the interlayer spacing of MMT was enlarged (from 1.27 to 2.13 nm) and its hydrophobicity was enhanced (contact angle from 48.14° to 105.6°). TiO2-MMT was added to epoxy resin (EP) to prepare a composite coating with multidimensional synergistic effect. The results show that the composite material can effectively fill the EP microhole defects, and the surface roughness of the coating is only 1.7 nm (pure EP is 65.5 nm). Electrochemical tests reveal that the corrosion current density (Icorr) was 1.126 × 10-5 A·cm-2, the protection efficiency was 98.40%, and the charge transfer resistance (Rct) reached 696.1 Ω·cm2, indicating that the coating effectively prolonged the diffusion pathways of corrosive ions through